La Fase preliminar del nuevo Proceso de Nulidad - Núñez González, Gerardo (Ius canonicum, 2017)
As part as the reform of the marriage annulment process stipulated in Motu Proprio Mitis Iudex, the Pope has ordered the establishment of a diocesan pastoral service to help the faithful who experience difficulties in their marriage. The functions of this pastoral service are manifold, depending on the marital status and needs of the faithful: to offer spiritual accompaniment; to mediate a possible solution to the marital crisis; to validate the marriage if possible; to guide spouses to the feasibility of a marriage annulment process. The structure and staff of this service will vary from diocese to diocese. Episcopal Conferences are encouraged to draw up a Vademecum that will ensure the integrity of such services.